High external quantum efficiency in InGaN-based green micro-light emitting diodes at ultra-low current density by removing pre-wells - Aimin Wang; Kaixuan Chen; Junyong Kang (Applied Physics Express)
InGaN-based green light-emitting diodes with different pre-well numbers were grown by an organometallic vapor phase epitaxy deposition method on patterned sapphire substrates. Micro-LED chips with a size of 17 × 20 μm ^2 were fabricated, and a peak external quantum efficiency (EQE) of 39% was achieved at ultra-low current density of 0.07 A cm ^−2 . The EQE variation curves of different samples were studied under different current densities. It was confirmed that by reducing the number of pre-wells the Shockley–Read–Hall non-radiative recombination under ultra-low current density was suppressed, which ultimately results in a high EQE of micro-LEDs.